Modulation of Blood Cell Activation by Four Commonly Used Anticoagulants - Engstad, Charlotte Sissener; Gutteberg, Tore Jarl; Østerud, Bjarne (Thrombosis and Haemostasis, 1997)
In the past years, our group has made several observations suggesting that blood cells behave differently and when stimulated, release different levels of cytokines, depending on which anticoagulant the blood has been drawn into. The aim of this study was therefore to compare the effect of the four anticoagulants EDTA, citrate, heparin and hirudin on monocyte, neutrophil (PMN), and platelet function in human whole blood. Human whole blood was employed as an ex vivo model of cytokine production and protein secretion, and lipopolysaccharide (LPS) induced tissue factor (TF) activity in monocytes and LPS induced tumor necrosis factor α (TNFα) release were chosen as parameters of monocyte activation. Platelet factor 4 (PF4) secretion and LPS induced lacto ferrin release were chosen as parameters of platelet and PMN activation, respectively. When human whole blood was stimulated with 5 ng/ml LPS for 2 h, TF activity in monocytes isolated from EDTA blood was found to be 2.9 mU/106 cells, whereas TF activity in monocytes isolated from citrated, heparinized and hirudinized blood was 14.7, 24.7 and 28.5 mU/106 cells, respectively. TNFα concentrations in platelet poor plasma (PPP) isolated from whole blood stimulated with 5 ng/ml LPS for 2 h was increased with 200,400 and 350% in citrated, heparinized and hirudinized blood respectively, as compared to EDTA blood. Next, the effect of the anticoagulant on PMN secretion was measured. PPP isolated from whole blood incubated with 5 ng/ml LPS for 90 min contained 1170 ng/ml (EDTA blood), 2880 ng/ml (citrated blood), 4220 ng/ml (heparinized blood), and 5520 ng/ml lactoferrin (hirudinized blood). When studying the platelet parameter PF4, whole blood was incubated without any stimuli for 60 min, and we found that heparin PPP contained 1180 ng/ml PF4, while hirudin PPP contained 469 ng/ml, citrate PPP 440 ng/ml, and EDTA PPP 217 ng/ml PF4, respectively. Finally, the low molecular weight heparin compound Fragmin had no enhancing effect on PF4 levels in whole blood. It is concluded that the anticoagulant used in in vitro experiments has a large influence on the parameters measured.